Предмет: Алгебра,
автор: IronFelix
Докажите тождество:
1) (a+b)²-4ab=(a-b)² 2)(a-b)²+4ab=(a+b)²
Заранее спасибо
Ответы
Автор ответа:
0
1)a^2+2ab+b^2-4ab=(a-b)^2
a^2-2ab+b^2=(a-b)^2
(a-b)^2=(a-b)^2
2) a^2-2ab+b^2+4ab=(a+b)^2
a^2+2ab+b^2=(a+b)^2
(a+b)^2=(a+b)^2
a^2-2ab+b^2=(a-b)^2
(a-b)^2=(a-b)^2
2) a^2-2ab+b^2+4ab=(a+b)^2
a^2+2ab+b^2=(a+b)^2
(a+b)^2=(a+b)^2
Похожие вопросы
Предмет: Английский язык,
автор: r6861377
Предмет: Другие предметы,
автор: Аноним
Предмет: Українська мова,
автор: SsPpmmQq
Предмет: Химия,
автор: basttak
Предмет: Экономика,
автор: Darina23